Analysis of the plant cover of RPPN Fazenda Uhumirim through remote sensing (Research, Society and Development, 2020)
This study aims to verify the vegetation conditions of the State RPPN Fazenda Nhumirim and its zone of influence in the maintenance of the natural environmental characteristics of a territory by comparing the vegetation cover of the years 1998 and 2017. All the work was done in a GIS environment with free and free software using the Normalized Difference Vegetation Index  and the Semiautomatic Classification Plug-in, available for installation in the add-ons. The results showed the efficacy of the Reserve in the preservation and increase of the phytomass inside the farm acquired by EMBRAPA, also demonstrating the complexity of the habitat, resulting from the great diversity of morphological and hydrological characteristics of the region in which the Fazenda, Nhecolândia's study base, keeps these characteristics more intensely.